1980
DOI: 10.1073/pnas.77.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic hormone-induced intracellular message: assay and partial characterization of an activator of DNA replication induced by epidermal growth factor.

Abstract: This paper explores the pathway from nuclear quiescence to mitogenesis. It describes an in vitro assay for an activator of DNA replication induced by epidermal growth factor (EGF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…As shown by Ohkuma & Poole (1978) this process results in an increase of pH to values outside the optimal range of the acid hydrolases and may thus interfere with lysosomal function. It has been proposed that continuous degradation or limited processing of ligand-receptor complexes by lysosomal enzymes is required to stimulate cell growth, one hypothesis being that this results in the production of a necessary intracellular messenger (Das, 1980;King et al, 1980). It is also possible that general lysosomal activity is essential for the lymphocyte to reprocess its constituents during activation and that inhibition of the acid hydrolases prevents this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Ohkuma & Poole (1978) this process results in an increase of pH to values outside the optimal range of the acid hydrolases and may thus interfere with lysosomal function. It has been proposed that continuous degradation or limited processing of ligand-receptor complexes by lysosomal enzymes is required to stimulate cell growth, one hypothesis being that this results in the production of a necessary intracellular messenger (Das, 1980;King et al, 1980). It is also possible that general lysosomal activity is essential for the lymphocyte to reprocess its constituents during activation and that inhibition of the acid hydrolases prevents this.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, chloroquine and other lysosomotropic amines have been shown to inhibit the mitogenesis of fibroblasts induced by epidermal growth factor (King etal., 1980). It is possible that degradation of the internalized ligand-receptor complex by the acid hydrolases in the lysosomes may be an essential step in the transduction mechanism of the mitogenic response to a ligand (Das, 1980). If this is so, then other simpler amines should be equally effective in inhibiting lymphocyte activation.…”
Section: Intoductionmentioning
confidence: 99%
“…Other studies have focused on growth factor-stimulated initiation of DNA synthesis by using nuclei from Xenopus laevis spleen cells (17) as a native DNA template. However, since Xenopus chromosomes may not have specific origins of replication (18), it is not clear whether stimulation ofXenopus nuclear replication by subcellular fractions from mitogenstimulated mammalian cells reflects critical cell-cycle control mechanisms operative in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have shown that spontaneously proliferating lymphoblastoid cells, PHA-stimulated human peripheral blood lymphocytes (PBL), and interleukin 2 (IL-2)-activated T cell blasts contain an extractable cytoplasmic protein called ADR Receivedfor publication 26 November 1985 and in revisedform 13 February 1986.…”
Section: Introductionmentioning
confidence: 99%
“…The assay used was a modification of the procedure of Das (13 15-min incubatiop at 0°C, the cultures were harvested as described above. The evidence that this assay measures DNA replication has been summarized (14), and includes the absolute requirement for ATP and the presence of replicative forks and "eyes."…”
Section: Introductionmentioning
confidence: 99%